Self-regulatory driving behaviours amongst older drivers according to cognitive status. (May 2016) - Devlin, Anna; McGillivray, Jane
Highlights: Older driver self-regulation and factors that influence self-regulation are not well understood. Self-regulatory driving behaviours were examined according to cognitive status. Passenger perspectives on older driver self-regulation were also obtained. Drivers with cognitive impairment appear to self-regulate more often compared to those without. Relevant factors that contribute to self-regulation are discussed. Abstract: Self-regulation of older drivers was explored according to their cognitive status in this pilot study by examining situations commonly avoided by older drivers. In addition, the role of driver insight on self-regulation was examined via passenger reports. Telephone interviews were conducted comprising 49 drivers aged 65 years and above and 40 passengers who acted as informants. Self-regulation was found to be common, with the majority of drivers (71.4%) reporting sometimes or always avoiding one of seven driving situations. However, drivers with cognitive impairment reported self-regulating more often than drivers without cognitive impairment. The largest discrepancy between passenger and driver reports of self-regulation behaviours was found for the drivers with cognitive impairment. These results possibly reflect a decreased awareness of self-regulatory driving behaviours in this subgroup of older drivers and may suggest that other external factors are contributing to self-regulation in older drivers with cognitive impairment. A discussion of these factors is provided with the aim of maintaining mobility and enhancing quality of life in this growing segment of the driver population.